Peran Pondok Pesantren dalam Pembinaan Akhlak Santri: Studi Kasus di Pondok Pesantren Baitul Arqom Al-Islami Kecamatan Pacet Kabupaten Bandung - Ihda Nabiila Farhah; M. Rachmat Effendi; N. Sausan M. Sholeh (UNISBA Press, 2022)
Abstract. The role of Islamic boarding schools is very influential in the formation of students' morals, by carrying out activities in Islamic boarding schools that run 24 hours in formal, informal and non-formal situations. This research aims to; 1) knowing the moral development of students at Baitul Arqom Islamic Boarding School, 2) knowing what methods are used in Islamic boarding schools, 3) knowing the results of students' moral development. The method used in this research is descriptive qualitative that uses several objects, namely: teachers, students and alumni. Data was collected by conducting observations, interviews, analysis and documentation. The results of the study show that Islamic boarding schools foster the morals of their students in daily life, which are provided with religious knowledge so that they can maintain good morals. The methods used at the Baitul Arqom Al-Islami Islamic Boarding School, namely: exemplary, general recitation, special recitation of students, and the discipline of praying in congregation. From the results of the interview that the moral development of the students went well and there was good cooperation from all components in the Islamic boarding school. Abstrak. Peran Pondok Pesantren sangat berpengaruh dalam pembentukan akhlak santri, dengan melaksanakan kegiatan di pesantren yang berjalan 24 jam dalam situasi formal, informal dan non formal. Penelitian ini bertujuan untuk; 1) mengetahui pembinaan akhlak santri di Pondok Pesantren Baitul Arqom, 2) mengetahui metode apa yang digunakan di Pondok Pesantren, 3) mengetahui hasil pembinaan akhlak santri. Metode yang digunakan dalam penelitian ini ialah kualitatif deskriptif yang menggunakan beberapa objek yaitu: Ustadz, santri dan alumni. Pengumpulan data dilakukan dengan mengadakan observasi, wawancara, analisis dan dokumentasi. Hasil dari penlitian menunjukkan bahwa pondok pesantren membina akhlak para santrinya dalam kehidupan sehari-hari, yang diberikan pembekalan ilmu agama agar dapat menjaga akhlak dengan baik. Metode yang digunakan di Pondok Pesantren Baitul Arqom Al-Islami, yaitu: keteladanan, pengajian umum, pengajian khusus santri, dan disiplin sholat secara berjama’ah. Dari hasil wawancara bahwa pembinaan akhlak santri berjalan dengan baik dan adanya kerjasama yang baik dari semua komponen yang ada di dalam pondok pesantren.